The UNEP Regional Seas Programme: An analysis of structure and process. - Jedynack-Copley, Maureen. (University of Ottawa (Canada), 1991)
The purpose of this research is to describe and analyze the structure and process of decision-making inherent in the United Nations' Regional Seas Programme (RSP). This programme applies a comprehensive management approach to marine and coastal areas, in formulating regional action plans which address a variety of coastal and water resource problems and issues. These action plans are formulated according to the needs of the region, as perceived by the governments concerned. The research product is a series of cogent observations and recommendations specifically related to the Regional Seas Programme and its structure and process. These pronouncements are related specifically to the elements of the Resource Management Assessment Model. Several conclusions were made for each element. Finally, the thesis returns to its premiere motivation: a concern for Arctic management. It is suggested that elements of the Regional Seas Programme may be suitable for the Arctic management experience. (Abstract shortened by UMI.)
Keywords: Geography.